THE USE OF A SPECIFIC GSRS QUESTIONNAIRE FOR DIFFERENTIAL DIAGNOSIS OF DISEASES OF THE GASTROINTESTINAL TRACT - Daniil D. Kazarin; Aleksey E. Shklyaev; Polina S. Bolkiseva; Ekaterina V. Petrova (Siberian Journal of Life Sciences and Agriculture, 2022)
The pathology of the gastrointestinal tract occupies one of the leading places in the structure of the general morbidity of the population. Despite modern diagnostic methods, their prevalence is constantly increasing. Among the diseases of the gastroenterological profile, the most common are chronic pancreatitis, gastric ulcer and duodenal ulcer, hepatitis and cirrhosis of the liver, as well as chronic intestinal diseases.